The Surgical Approach Visualization and Navigation (SAVN) System reduces radiation dosage and surgical trauma due to accurate intraoperative guidance. Issue 4 (April 2019) - Jiang, Ying; Wang, Hong-Rui; Wang, Pan-Feng; Xu, Shuo-Gui
Highlights: Compared to the C-arm, the SAVN System significantly reduces the screening time during surgery, which is mainly due to reduce radiation attempts. For patients, the SAVN System drops both direct and scatter radiation dose as compared to that of the C-arm. The SAVN System decreases the radiation dose for the primary surgeon as compared to that of the C-arm. Abstract: Object: The intraoperative fluoroscopy has been widely used in modern neuro-spinal surgery due to the overwhelming trend toward minimal-access surgery. However, both patients and surgical personnel were under ionizing-radiation exposure during fluoroscopy usage. Since the fluoroscopy constitutes the vast majority of radiation exposure for both surgeons and patients, the development and improvement of new interventional possibilities are of great importance and interests. Patients and methods: A total of 20 patients were included in the current study, who received thoracic-spinal tumor resection via posterior midline approach. In comparison to the conventional C-Arm mobile fluoroscopy machine, theS urgical Approach Visualization and Navigation (SAVN) System was used to evaluate the effectiveness in reducing radiation. Results: The pain intensity and Japanese Orthopedic Association Score were equally ameliorated in patients of two groups. However, compared to C-arm group, the SAVN significantly reduced the screening time from 26.8+ 12.4 to 17.1+ 9.2 s (36.2% radiation reduction, P < 0.05), which was mainly due to the significant reduction of radiation attempts (from 12.8+ 4.9 to 7.1+ 5.5 times, P < 0.05). For patients, the direct and scatter radiation dose dropped 30.4% ( P < 0.05) in the surgical region and 47.6% ( P < 0.01) in the non-surgical region by using the SAVN System. Additionally, the tumor diameter/skin incision ratio increased from 0.39+ 0.4 to 0.47+ 0.28 after SAVN usage. Meanwhile, thedosimeter showed that the radiation dose to the primary surgeon was also lower in the SAVN group (72.1% reduction, P < 0.01). Conclusion: Comparing the conventional C-arm, the SAVN System based thoracic-spinal surgery significantly lowered radiation duration and dosage application towards both surgeons and patients.